OZONE MICRO-BUBBLE WATER (OMBW) SEBAGAI SENYAWA PENYANITASI DAGING AYAM MENTAH TERHADAP Salmonella spp. DAN PENGARUHNYA SELAMA PENYIMPANAN PADA SUHU MENYIMPANG - Ryan Pieter I Nalle; Ni Luh Putu R. Cakswindryandani; Siska Elvani (JURNAL AGRISA, 2023)
Ozone micro-bubble water (OMBW) can be used as sanitizer to wash fresh food products in order to eliminate microbiological contamination. A trial was carried out to determine the effectiveness of OMBW as a washing solution for raw chicken breast on the growth and concentration of cocktail mix Salmonella spp. (S. Enteritidis DMST 15676, S. Derby DMST 16879, S. Newport DMST 15675 and S. London DMST 7110). The washing treatment was carried out by dipping the artificially contaminated raw chicken breast in 1 and 2 ppm of OMBW or sterilized water (control) and shaken at 80 rpm for 5 minutes. The samples were kept at 4°C for 24 h before being exposed to the temperature abuse condition. The temperature abuse condition was carried out continuously from 10° C for 4, 6 and 8 h up to 30° C for 2 h. After the washing process, Salmonella spp. was greatly reduced by 1 and 2 ppm OMBW, significantly different (P<0.05) from washing with sterilized water. Washing with 1 ppm OMBW, 2 ppm OMBW and sterilized water reduced the Salmonella spp. by 0.86, 0.72 and 0.41 log CFU/mL, respectively. Storage of raw chicken fillet at the recommended temperature of 4° C for 24 h, inhibited the growth of Salmonella spp. in samples that had previously been washed with 1 and 2 ppm OMBW, while samples washed with sterilized water showed a slight increase in Salmonella spp. numbers, but was not significantly different (P>0.05) from the other treatments. At the end of temperature abuse storage, the Salmonella spp. concentration in all samples increased from the initial counts.